1990
DOI: 10.1002/jcp.1041440219
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocyte growth factor activity on proliferation and differentiation of human keratinocytes: Differentiation response distinguishes KGF from EGF family

Abstract: Human keratinocyte growth factor (KGF) is an epithelial cell specific mitogen which is secreted by normal stromal fibroblasts. In the present studies, we demonstrate that KGF is as potent as EGF in stimulating proliferation of primary or secondary human keratinocytes in tissue culture. Exposure of KGF- or EGF-stimulated keratinocytes to 1.0 mM calcium, an inducer of differentiation, led to cessation of cell growth. However, immunologic analysis of early and late markers of terminal differentiation, K1 and fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 35 publications
13
135
1
Order By: Relevance
“…In fact, it has been known that KGF induces cell differentiation and suppresses cell proliferation in some cases. For example, KGF is known to promote the differentiation of keratinocytes derived from human neonatal foreskin 24,25 as well as human lung squamous cell carcinoma. 26 In human salivary gland tumors, loss of KGFR expression was observed in the process of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been known that KGF induces cell differentiation and suppresses cell proliferation in some cases. For example, KGF is known to promote the differentiation of keratinocytes derived from human neonatal foreskin 24,25 as well as human lung squamous cell carcinoma. 26 In human salivary gland tumors, loss of KGFR expression was observed in the process of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, KGF is known to have diverse effects, such as inhibition of apoptosis [21][22][23] and regulation of cell differentiation. [24][25][26] To help clarify these issues, it is desirable to localize KGF and KGFR at a cellular level in tissue sections of human breast cancer. Although KGF mRNA expression in ruminant mammary gland was previously detected by in situ hybridization using autoradiography, 27 there have been no reports on immunohistochemical analysis of KGF and KGFR expression in human breast cancer tissue.…”
mentioning
confidence: 99%
“…However, other experimental approaches will be required to fully define the precise nature of KGF involvement in epithelial development. In this regard, earlier cell and organ culture studies have demonstrated that KGF is a paracrine mitogen for epithelial cells from a variety of different sources (Aaronson et al, 1991;Marchese et al, 1990;Pierce et al, 1994;Rubin et al, 1989;Ulich et al, 1994), as well as a morphogen in the ductal branching morphogenesis of the neonatal mouse seminal vesicle (Alarid et al, 1994) and the neonatal rat prostate (Sugimura et al, 1993). The extension of similar studies to other organ systems will provide a powerful approach in further elucidating the multiple roles of KGF during development.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-7 is a potent mitogen for keratinocytes and has also been shown to modulate differentiation (13,41). Primary cultures of human keratinocytes in basal medium were treated with 5 ng/ml FGF-7 in the presence of heparin or DS.…”
Section: Dermatan Sulfate Enhances the Proliferative Effect Of Fgf-7 mentioning
confidence: 99%